Serological prevalence of hepatitis B virus (HBV) in Mardan district, Khyber Pakhtunkhwa, Pakistan - Ullah,N. (2022)
Abstract Hepatitis B virus infection is perilous among the five types of Hepatitis, as it remains clinically asymptomatic. The present study draws up-to-date prevalence of Hepatitis B virus (HBV) in the general population of Mardan, Khyber Pakhtunkhwa Pakistan. The blood samples from 4803 individuals including 2399 male and 2404 females were investigated. All the suspected samples were analyzed for hepatitis B surface antigen using Immuno-chromatographic test (ICT), Enzyme-linked immunosorbent assay (ELISA), and followed by Reverse transcription-polymerase chain reaction (RT-PCR). Results showed that 312 (13.00%) out of 2399 individuals contained antibodies in their blood against HBV, while among the different age groups, the highest incidences of HBV antibodies were found in the age of 21-30 groups (10.73%). Furthermore, the ICT positive samples were screened by nested polymerase chain reaction to detect the existence of active HBV-DNA. It was observed that 169 (7.04%) out of (2399) male of the total population (4803) tested was positive. On the other hand, the female 463 (19.25%) possessed antibodies in their blood against HBV. Accumulatively, our results showed a higher percentage of HBV prevalence in males than females in the age group 21-30 years. The total HCV infected in Mardan general population was recorded at 5.7% comprising both male and female.